2022
DOI: 10.33594/000000535
|View full text |Cite
|
Sign up to set email alerts
|

Set7 Deletion Prevents Glucose Intolerance and Improves the Recovery of Cardiac Function After Ischemia and Reperfusion in Obese Female Mice

Abstract: Background/Aims: An obesogenic diet (high fat and sugar, low fiber) is associated with an increased risk for metabolic and cardiovascular disorders. Previous studies have demonstrated that epigenetic changes can modify gene transcription and protein function, playing a key role in the development of several diseases. The methyltransferase Set7 methylates histone and non-histone proteins, influencing diverse biological and pathological processes. However, the functional role of Set7 in obesity-associated metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Since Set7 is critical for calcium handling in cardiomyocytes and loss of Set7 affects cardiomyocyte contractile activity [42], it is possible that prolonged exposure to isoproterenol might impact calcium transients and myocardial function. Recently, we demonstrated that loss of Set7 improves the recovery of cardiac function after I/R injury in obese female mice [22]. Therefore, our results indicate that Set7 plays a key role in cardiac dysfunction in response to different stimuli.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Since Set7 is critical for calcium handling in cardiomyocytes and loss of Set7 affects cardiomyocyte contractile activity [42], it is possible that prolonged exposure to isoproterenol might impact calcium transients and myocardial function. Recently, we demonstrated that loss of Set7 improves the recovery of cardiac function after I/R injury in obese female mice [22]. Therefore, our results indicate that Set7 plays a key role in cardiac dysfunction in response to different stimuli.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, streptozotocin-induced type 1 diabetic rats exhibit higher Set7 protein levels in the heart [21]. Recently, we also identified that Set7 protein levels are increased in the hearts of obese female mice [22]. Together, these studies suggest that Set7 may influence cardiac morphology and function.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation